Des cités hallucinées à la grille invisible, William Gibson et les métamorphoses du cyberespace - Henri Desbois (ReS Futurae)
The influence of William Gibson has been of the utmost importance in crafting and spreading many popular imaginaries associated with digital technologies. In his first novels, cyberspace is at the same time a narrative trick to depict a global computer network and an element of a more global investigation of the relationship between geographic space and technology. Between 2003 and 2010, Gibson has published three novels set in the contemporary world, thus apparently relinquishing the SF genre. He nonetheless continues his exploration of the very same topics than in his former novels, recasting cyberspace as a way to envision the technological changes of the last two decades. More specifically, the novel Spook Country uses the image of the “eversion” of cyberspace to describe the way ubiquitous computing is invading urban space. Cyberspace can simultaneously be a purveyor of simulacra, through virtual reality technology, and an invisible agent ensnaring the city in its wireless nets. It provides a particularly fertile ground for the paranoid strain of our contemporary culture.